2022
DOI: 10.19184/nlj.v7i2.28010
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Preparedness Information among Emergency Nurses and Its Relationship with Disaster Preparedness

Abstract: Nurses are health workers who play an essential role in disaster management, so the right strategy is needed in disaster preparedness. Management of disaster is an intervention in the Emergency Department (ED) that has an essential role in preparedness, emergency responses, and recovery to reduce the effects during and after the disaster. Emergency preparedness information in the ED has a scope like triage and first aid, biological agent detection, accessing critical resources and reporting, the incident comma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…However, Hamid et al emphasized the critical role of managers in disaster risk management, including their commitment to providing facilities and resources, leading and coordinating educational activities, and creating motivation and dynamism among nurses [ 48 ]. The lack of skills and competencies of nurses during disasters is more related to reporting methods and access to information, incident command system, knowledge about epidemiological and biological factors, communication, and teamwork [ 49 , 50 ]. The study identified several barriers to effective disaster risk management, including the unavailability of evidence, a shortage of disaster nursing professionals, and a lack of use of research evidence to prepare clinical evidence-based guidelines for disaster risk management.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hamid et al emphasized the critical role of managers in disaster risk management, including their commitment to providing facilities and resources, leading and coordinating educational activities, and creating motivation and dynamism among nurses [ 48 ]. The lack of skills and competencies of nurses during disasters is more related to reporting methods and access to information, incident command system, knowledge about epidemiological and biological factors, communication, and teamwork [ 49 , 50 ]. The study identified several barriers to effective disaster risk management, including the unavailability of evidence, a shortage of disaster nursing professionals, and a lack of use of research evidence to prepare clinical evidence-based guidelines for disaster risk management.…”
Section: Discussionmentioning
confidence: 99%